Socio-Cultural Factors in Mamar Management Impacting Ecosystem Services - Ngaji, Alfred Umbu Kuala; Benu, Yason Edison; Wardhana, Laurentius D Wisnu (Faculty of Geography, Universitas Gadjah Mada, 2025)
Changes in the earth's landscape is causing significant transformations impacting ecosystem services globally. One notable consequences of these changes is trade-off in ecosystem services, which is caused by human land use activities due to social and cultural perspectives of society. Therefore, this research aimed to understand the influence of socio-cultural factors that impact ecosystem services in Mamar management. The experiment was conducted using as qualitative and quantitative survey to identify changes in Mamar management through participatory research and land use analysis on Landsat 2013 and 2023. Socio-cultural factors were also identified through an ethnographic method using Smart PLS 3.2.7. The results showed that there was a change in the priority of ecosystem services, as supported by changes in land use and the importance index of Piper aduncum L. and Areca catechu. Several factors showing significant influence were Socio-Demographic-Economic Conditions (SDE4, SDE5, SDE6), Socio-Economic Vulnerabilities (KR6, KR7, KR8, KR9), and Cultural Resilience (RSB1, RSB2, RSB3) in Mamar management (SP1, SP2), which affected the production of ecosystem services. Based on the results, understanding patterns of social influence enabled appropriate mitigation strategies for imbalances in ecosystem services.Received: 2024-06-23 Revised: 2024-06-28 Accepted: 2025-04-16 Published: 2025-04-29